Utilization of the Profile Matching Method for Recommendations for the Appointment of Honorary Teachers to Become Permanent Teachers - Febriyanto, R Tri Hadi; Wanto, Anjar; Damanik, Bahrudi Efendi (Yayasan Literasi Sains Indonesia, 2023)
This study aims to utilize the Profile Matching method in the recommendation process for hiring honorary teachers to become permanent teachers at Taman Siswa Bah Jambi Private High School. Honorary teachers are an important part of the education system in Indonesia, and recommendations for their appointment as permanent teachers require the right approach to ensure fair and efficient selection. In this study, an analysis of the Profile Matching method was carried out in assessing the feasibility and integrity of honorary teachers. Data collection was carried out by collecting information on academic achievement, teaching experience, and other qualifications of honorary teachers at Taman Siswa Bah Jambi Private High School. The results of the study show that Profile Matching provides recommendations that are quite relevant and can be considered in the appointment of honorary teachers to become permanent teachers. The Profile Matching method tends to place more emphasis on suitability of teaching qualifications and experience. This research is expected to provide valuable information for related parties in choosing the appropriate method for recommendations for hiring honorary teachers to become permanent teachers at Taman Siswa Bah Jambi Private High School.